Prevalence of The Most Common Disease Among the Community in Gili Iyang, Sumenep, Madura Island - Athiyyah, Alpha Fardah; Sulistiawati, Sulistiawati; Fatimah, Nurmawati; Dewanti, Linda; Christian Susianto, Steven; Edi Suharno, Novianto (Publikasi Indonesia, 2025)
Indonesia is currently experiencing a shift in disease trends, this is marked by an increase in the prevalence of non-communicable diseases (NCDs). The prevalence of these NCDs is also increasingly observed among younger age groups due to rising risk factors such as overweight and obesity. This study aimed to determining the prevalence of the most common diseases and the health profile of the community in Gili Iyang, Sumenep. The samples included in this study were participant in Airlangga Community Hub 2024 in Gili Iyang Island, Sumenep Regency. There were several services in this community development including anthropometry measurement, physical examination and simple lab test. Data was collected and processed using a data processing application, Microsoft Excel. A total of 114 participant were included in this study, hypertension was the most prevalent disease during the community development program 30.1%, followed by hypercholesterolemia as the second most common condition 28.16%, and myalgia as the third leading cause of illness 17.48%. Urgent need for comprehensive health interventions, including routine screening, early management, and targeted health education programs to address the growing burden of NCDs.